Aromaten im Blut mittels Headspace‐Gaschromatographie mit massenspektrometrischer Detektion [Biomonitoring Methods in German language, 2018]. Issue 2 (24th April 2018) - Göen, T.; Müller, J.; Hoppe, H.‐W.; Hartwig, A.; ,
Abstract: The working group „Analyses in Biological Materials" of the Permanent Senate Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area verified the presented biomonitoring method. The here described analytical method enables the simultaneous determination of benzene, toluene, chlorobenzene, ethylbenzene, o‐xylene, m‐xylene, p‐xylene, styrene, n‐propylbenzene, isopropylbenzene (cumene), 1, 2, 3‐trimethylbenzene (hemimellitene), 1, 2, 4‐trimethylbenzene, 1, 3, 5‐trimethylbenzene (mesitylene) and 1, 2, 3, 5‐tetramethylbenzene (isodurene) in blood. For determination, the blood samples are introduced into headspace vials. The vials are sealed and heated to 50 °C in the autosampler. Subsequently, an aliquot of the vapour phase is injected into the GC system and analysed using mass spectrometry. Calibration standards are prepared in ovine blood and processed in the same way as the samples to be analysed.